PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS PjBL MENGGUNAKAN PERMAINAN TTS PADA POKOK BAHASAN BARISAN DAN DERET DI MTS AL -MUTTAQIN - Bela Apriliani; Amin Harahap; Laili Habibah Pasaribu (Universitas Bhinneka PGRI, 2025)
Open modules are educational tools designed to support independent learning planning. This study employed quantitative descriptive methods on a population of class IX MTS YP AL-MUTTAQIN students in the odd semester of the 2024/2025 academic year, which consisted of 35 students. The data was analyzed using SPSS 24 software, which included multiple linear regression testing. The study's findings indicate that, partially or based on the T-Test, the Project Based Learning (PBL) Mathematics Learning Module variable has a positive influence on the Crossword Game variable. This is supported by the fact that Tcount Ttable and a significance level of 0.000. Aside from that, the F test yields significant results with a p-value of 0.000, indicating a strong relationship between variables.